THE EFFECT OF INDEPENDENT COMMISSIONER ON REAL EARNINGS MANAGEMENT WITH THE MODERATION OF POLITICAL CONNECTION - Auliana, Rini Adriani; Cahyani, Arie; Khairunnisa, Khairunnisa (Economic Education, University of Jember, 2024)
This study aims to examine the political connection in moderating the effect of independent commissioners on real earnings management and to examine real earnings management uses to avoid earning decreases. This study uses a quantitative approach. The population is manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020. Using the purposive sampling method, 306 observation firms were determined. Hypothesis testing was carried out using multiple linear regression and hierarchical regression analysis. The results showcased that real earnings management proxy abnormal cash flow of operation used to avoid earning decreases. Independent commissioners can be used to reduce real earnings management proxy abnormal production cost and political connection can't moderate the effect of independent commissioners on real earnings management.